Community Perception of Social Media Marketing Activity on Instagram @VisitJawaTengah - Ratri Primayani Sholihat (Fakultas Seni Rupa dan Desain ITB, 2023)
The use of social media has become a popular online activity. One of the most popular social media platforms is Instagram. Therefore, companies, institutions, and other tourism stakeholders mostly choose Instagram as the promotion medium. Promotion through Instagram is one form of social media marketing activity (SMMA). SMMA consists of several aspects, such as entertainment, customization, interaction, electronic word of mouth (e-WoM), and trendy. This study aims to determine the public’s perception of the social media marketing activity on Instagram (@VisitJawaTengah) during the COVID-19 pandemic in 2021. The research method used is descriptive-quantitative. The results of the study show that people have a positive perception of social media marketing activities on Instagram (@VisitJawaTengah).